CULTURAL AND PHILOSOPHICAL DISCOURSE ON THE CONCEPT OF MANIPULATION (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2025)
The article is devoted to a variety of linguistic manipulation, a description of the work of discursive mechanisms of manipulative influence. The article presents the specific features of manipulative discourse, examines discursive manipulation in a broad and narrow sense, and characterizes its varieties. The author identifies and describes the linguistic means by which hidden psychological effects are carried out. The need for such a study is due to the socio-cultural situation, which provides a favorable basis for the use of various information technologies.Recently, language has been perceived not only as a means of communication, a system of verbal signs, but also as a way of interaction based on certain tactics and strategies.Since the flow of information from various sources is constantly growing, the phenomenon of manipulation is a very important object of study from the point of view of psycholinguistics.